Parental styles and harsh parenting in a sample of Mexican women: A structural model - Frías-Armenta, Martha; Sotomayor-Petterson, Marcela; Corral-Verdugo, Víctor; Castell-Ruiz, Irasema (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
One-hundred and fifty Mexican women were interviewed in regard to their parental beliefs and practices, their level of depression, their degree of autonomy, how much they punished their children, and their perceptions about the effects of child punishment. Factors representing such constructs were specified within a structural equations model, and their relations were calculated. Results revealed that an authoritarian parental style had a significant, positive and direct effect on punishing children, but the authoritative style did not. The level of women’s depression, as well as the perception of punishment benefits, positively influenced child punishment, while the perception of punishment costs negatively affected harsh parenting. In turn, disciplinary parental beliefs positively affected authoritarian style and negatively affected women’s autonomy in family decisions, while this autonomy inhibited authoritarian parenting.